The Routledge handbook of vocabulary studies: A study in micro-bibliometrics - Meara , Paul (Studies in Second Language Learning and Teaching, 2023)
This paper reports a bibliometric analysis of two small data sets: a set of 34 papers that make up The Routledge handbook of vocabulary studies (Webb, 2020) and a set of papers dealing with second language (L2) vocabulary research taken from a single journal Frontiers in Psychology. Bibliometric maps based on author co-citations in these two data sets are presented and compared. Although the two data sets are comparable in terms of size, they appear to be very divergent. In particular, the significant sources identified in The Handbook map seem to play a relatively minor role in the Frontiers map. The obvious conclusion is that The Handbook is not as representative of L2 vocabulary research as its title might lead us to believe. The paper argues that micro-bibliometric studies like this one can sometimes highlight features that are lost in the more traditional large-scale bibliometric approach.